The effect of torbangun plant (Coleus amboinicus Lour) active substances on lactation in mice - Risch, Awalludin (2013)
The main purpose of this research is to investigate the effects of active ingredients in the Torbangun plant to the mice lactation milk glands production. Torbangun leaves were extracted using soxhlet. The quantitative analysis of the extracted Torbangun leaves were analyzed by Gas Chromatography-Mass Spectrometry (GC-MS).The Fourier Transform Infra Red spectroscopy (FTIR) was applied to examine the functional group of the extracted samples; antibiotic screening tests was performed by the paper disk method; total phenolic content, total flavonoid content and antioxidant activity were analyzed using UV Vis-Spectrophotometer; heavy metals content was determined using ICPMS; Clinical trials were carried out on 36 mice which consisted of six control mice and each six mice were treated with 1%, 5%, 10, 15% and 20% of extracted Torbangun leave and mammary glands of mice were observed by histological analysis. The results indicated that the compounds in extracted Torbangun leave were phenol (PHE), gamma sitosterol, campesterol, Isocholesteryl methyl ether, Octadecanoic acid, Stigmasterol, Benzoic acid, 1,2-Benzenediol, phenol, 3-methoxy-2,4,5-trimethyl and alpha-amyrin; the functional group of extracted Torbangun leave were alcohol, ether, carboxylic acids and esters, aromatic rings and alkenes; antibiotic families determined in extracted Torbangun leaves were penicillin, tetracycline, aminoglycoside and macrolide; total phenolic content, total flavonoid content and antioxidant activity were 206.087 mg/L, 82.814 mg/L and 3.68 mg/L, respectively and heavy metals content in extracted Torbangun leaves were As (0.1 ppm), Pb (2.39 ppm), Cd (0.07), Mg (23.38 ppm) and Cu (15.42 ppm). The results of clinical trials showed that the differences between control mice and mice consumed with extracted Torbangun leave (1%, 5%, and 10%) for milk production were not significant, while the differences of the control mice and mice consumed with extracted Torbangun leave (15%, control and 20%) for milk production were significant. The histology of mammary glands for mice treated with 1%, 5% and 10% of extracted Torbangun leave exhibited equivalent to control mice.. While the mice treated with 15% and 20% of extracted Torbangun leave showed a lot of milk in the lobules (mammary gland). In conclusion, the active substances in extracted Torbangun leave influenced the function of lactating mammary gland, which consequently may increase milk production and it was proven safe for human consumption.